Portée et limites des travaux de psychologie cognitive pour l’étude du développement et du fonctionnement vocationnel - Huteau, Michel (Canadian Journal of Counselling and Psychotherapy, 2011)
In order to develop, vocational psychology needs to interact with other sectors of the field. This study examines the interaction between vocational psychology and cognitive psychology. The concepts, theories and models of the latter are likely to be more precise than those of vocational psychology. Even though it may be advantageous to inspire ourselves from cognitive psychology, it is generally impossible to simply transpose concepts and models. These considerations are illustrated via two themes: professional representations and processing of these representations in order to elaborate project preferences.